Positive interaction of industrial and recycled steel fibres in fibre reinforced concrete - Bjegovic, Dubravka; Baricevic, Ana; Lakusic, Stjepan; Damjanovic, Domagoj; Duvnjak, Ivan (Journal of Civil Engineering and Management, 2014)
In line with current ”green” transport initiatives, Croatia plans to build over the next investment period a high speed railway line which will connect central Croatia and its capital with coastal regions of the country. According to design documents, the track system will be built using ballastless concrete solutions. In the scope of the project “Concrete track system – ECOTRACK”, researchers from the University of Zagreb – Faculty of Civil Engineering analysed a new material, i.e. the rubberized hybrid fibre reinforced concrete (RHFRC), in order to find out whether its properties are adequate for the proposed concrete track system. The RHFRC contains by-products from mechanical recycling of waste tyres (rubber and steel fibres). The study of fibre and rubber interaction and their contribution to mechanical properties of the fibre reinforced concrete is presented, as extensive research on positive interaction between industrial and recycled steel fibres has not as yet been made. The results show that the RHFRC is an innovative, sustainable and cost-effective concrete, which is fully compliant with criteria prescribed in relevant standards.